Clinical Profile of Acute Pancreatitis in Children in a Tertiary Level Hospital of Bangladesh - Musabbir, Nadira; Karim, ASM Bazlul; Mazumder, Md Wahiduzzaman; Sultana, Kaniz; Anwar, Syeda Afria; Haque, Md Ariful; Hussain, Faika (Bangladesh Journal of Child Health, 2017)
Background: Acute pancreatitis is an acute inflammatory condition of the pancreas that may extend to local and distant extrapancreatic tissues. The incidence of acute pancreatitis in children has increased significantly in the past two decades. It can be associated with severe morbidity and mortality. It should be considered in every child with unexplained acute abdominal pain. Objectives: To observe the clinical, biochemical and imaging profiles of acute pancreatitis in children. Methods: It was a cross-sectional study conducted at the Department of Pediatric Gastroenterology & Nutrition of Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2014 through June 2015. A total of 50 cases of acute pancreatitis were included in this study. The diagnosis of acute pancreatitis was based on diagnostic criteria of acute pancreatitis made by INSPPIRE group (If a child had any 2 of the 3 criteria: the abdominal pain compatible with acute pancreatitis, elevated serum amylase and /or lipase level more than three times of upper limit of normal, imaging findings compatible with acute pancreatitis). Clinical characteristics, laboratory and imaging profile of the cases, complications were studied. Results: Among 50 cases, male were 46% and male female ratio was 0.8:1. Mean age at presentation was 10.2 ± 3.2 years. Forty eight (96%) patients had abdominal pain which was severe agonizing in 81.3% cases. The common location of pain was in epigastric region (77%). Pain radiating to back in 22.9% patients. Mean duration of pain was 6.6 ± 4.4 days before hospital admission. Vomiting was present in 72% patients followed by fever (30%). Two (4%) patients had jaundice. Ascites was noted in 12% patients and abdominal mass in 6% patients. Out of 50 cases of AP, biliary sludge was associated in 6% patients, biliary ascariasis in 4%, choledochal cyst in 2% and gallbladder stone in 2% patients. But in this study, 4% patients had Wilson disease. Laboratory tests showed leukocytosis in 28% patients, high serum amylase and lipase level in 56% and 58% patients respectively. Postive findings in ultrasonogram were present in 66% patients. In the present study, hypocalcemia was found in 38% patients, pseudocyst in 6% and pancreatic necrosis in 2% patients. Conclusion: Although acute pancreatitis may present with varieties of clinical feature, the most common one is abdominal pain and common location of pain is in epigastric region. For confirmation of clinically diagnosed pancreatitis, both serum amylase and lipase level and abdominal ultrasound are useful tools. Bangladesh J Child Health 2016; VOL 40 (3) :160-165